Efficacy of COVID-19 Vaccine (Journal of Preventive and Social Medicine, 2022)
With the onset of the novel coronavirus, scientists and medical professionals worked tirelessly to develop an effective clinically approved vaccine for the same. Initially what seemed impossible is now a reality and not only have experts manufactured COVID vaccines in such a short span of time, but they have also developed different types and versions of it too. Equitable access to safe and effective vaccines is critical to ending the COVID- 19 pandemic, so it is hugely encouraging to see so many vaccines proving and going into development. WHO is working tirelessly with partners to develop, manufacture and deploy safe and effective vaccines. Safe and effective vaccines are a game-changing tool. Being vaccinated does not mean that we can throw caution to the wind and put ourselves and others at risk, particularly because research is still ongoing into how much vaccines protect not only against disease but also against infection and transmission. But it’s not vaccines that will stop the pandemic, rather it’s vaccination with proper efficacy. Out of more than 100 research articles on COVID-19 and SARS-CoV-2 vaccines 41 articles were included in the present study. As of 1 May 2021, there have been 152 661 445 Covid-19 cases with 3 202 256 deaths globally. This pandemic led to the race to discover a safe and effective vaccine to achieve herd immunity and curtail the damaging effects of Covid-19. This study aims to discuss the most recent WHO-approved Covid-19 vaccine subtypes, their trials, doses and efficacy. As of 16 May 2021, the number of countries that have approved the use of the following vaccines is Pfizer in 85, Moderna in 46, Oxford/AstraZeneca in 101, and Janssen in 41.JOPSOM 2021; 40(2):65-72